TEMPAT SAMPAH OTOMATIS BERBASIS ARDUINO UNO DI KANTOR DESA BONTOMACINNA KABUPATEN BULUKUMBA - Haerunnisa (LPPM STMIK BINA ADINATA, 2020)
This study aims to: (1) design an automatic garbage bin system based on Arduino Uno so that it can open and close the trash can automatically. (2) find out the capacity of the trash can when it is full of Phone and SMS (Short Message Service) notifications that are connected directly to the janitor via the GSM Module. This research uses Action research method (Action Research) one from of design research, in action research the research the researchers describe, interpret, and explain a social situation at the time of a spectrum simultaneously with making a change or intervention with the purpose or inventation with the purpose of improvement or participation. Based on the test results, it can be concluded that using Arduino Uno R3 as the control center of the circuit, ultrasonic sensor 1 as an object arrival detector, ultrasonic sensor 2 as a trash can capacity detector, servo motor as the opening and closing of the trash can and a GSM module as an SMS (Short Message) notification sender. Service) then created a trash can that can open and close automatically and can provide SMS notifications to cleaners